How to manage a congenital heart defect in a patient with thrombocytopenia-absent radius syndrome? TAR syndrome and heart defect - İştar, Hande and Harmandar, Buğra (Journal of Surgery and Medicine, 2024)
Ventricular septal defect (VSD) can be repaired using cardiopulmonary bypass, resulting in a favorable postoperative outcome with minimal bleeding. Thrombocytopenia-absent radius (TAR) syndrome is rare, occurring in approximately 0.42 out of 100,000 live births. This syndrome is characterized by hypo-megakaryocytic thrombocytopenia and bilateral absent radii. TAR syndrome can be life-threatening within the first 14 months of life due to severe bleeding. In this report, we present the case of a 4-month-old male patient diagnosed with both VSD and TAR syndrome. We describe the surgical management of the VSD as well as the perioperative treatment for hemorrhagic diathesis.